Modelli di business emergenti nella moda sostenibile: l’innovazione nel caso di un’organizzazione nonprofit - Runfola, Andrea; Gigliotti, Marina; Picciotti, Antonio (Piccola Impresa / Small Business, 2020)
This article addresses the dynamics of sustainable fashion from an original perspective, that of a nonprofit organization with entrepreneurial orientation. Combining circular economy, through the re-use of stock of fabrics, and social activities, such as the employment of disadvantaged people, the organization is able to propose fashion items that are sold in traditional fashion retail channels. The article investigates the main components of the business model, pointing out implications emerging from the hybrid nature of the company and the relationships with profit firms. Based on the discussion of four main elements that characterize the business model, the article highlights the emerging opportunities in the fashion system, for actors such as the nonprofit organization analyzed, to be a focal actor in innovative proposals, which considers sustainability as a main driver of value offered to the market.